Pattern and Etiology of Mandibular Fractures Reported at Nepalgunj Medical College: A Prospective Study - Kansakar, Niva; Budhathoki, Bikram; Prabhu, Namdev; Yadav, Anjani Kumar (Journal of Nepalgunj Medical College, 2017)
Background: Mandibular fracture is one of the most common fractures of the maxillofacial region. The pattern of mandibular fractures varies from country to country and these variations can be due to social, cultural, and environmental factors. Objectives: This study was conducted to evaluate the etiology, incidence and pattern of mandibular fractures in western region of Nepal, reported at Nepalgunj Medical College Teaching Hospital.Methodology: A prospective study of 130 patients with mandibular  fractures  was  conducted  in  Department  of  Dentistry,  Nepalgunj  Medical  College  Teaching  Hospital  from  November  2013  to November 2014. These patients were examined both using clinical and radiographic parameters for mandibular fracture. Data concerning age, gender, causes of fracture and sites of fracture were analyzed.Result: Out of 130 patients, 104(80%) were male patients and 26(20%) were female patients. Most common age group was between 21-30 years. Most common cause of mandibular fracture was road traffic accidents accounting for 66(50.77%) cases followed by fall injury in 30(23.08%) cases. Most common site involved was parasymphysis 46(30.47%) followed by angle 27(17.89%).  Road traffic  accidents due to alcohol  consumption 40(68.97%) was the leading cause followed by assault 10(17.24%) and fall 8(13.79%).Conclusion: Mandibular fractures are more frequent  in  male  than  female  with  higher  frequency  in  21-30  years  age  group.  The most commonly fractured site was the parasymphysis. Road traffic accidents were the most common etiology and significantly associated with alcoholism. JNGMC Vol. 13 No. 2 December 2015